2021
DOI: 10.1021/acs.analchem.0c04547
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Anchored Molecular Thermometer Quantitatively Monitoring Cellular Inflammations

Abstract: Temperature in mitochondria can be a critical indicator of cell metabolism. Given the highly dynamic and inhomogeneous nature of mitochondria, it remains a big challenge to quantitatively monitor the local temperature changes during different cellular processes. To implement this task, we extend our strategy on mitochondria-anchored thermometers from “on–off” probe Mito-TEM to a ratiometric probe Mito-TEM 2.0 based on the Förster resonance energy transfer mechanism. Mito-TEM 2.0 exhibits not only a sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 61 publications
(83 reference statements)
1
35
0
Order By: Relevance
“…The abovementioned results demonstrate that a large temperature difference exists in the local nano‐microregion of the lipase, which is consistent with the results reported in other studies (e.g., temperature change in mitochondria [ 19,20 ] ). The dispute about the data of temperature change in nano‐microregion indicates that the understanding of the phenomenon is different.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The abovementioned results demonstrate that a large temperature difference exists in the local nano‐microregion of the lipase, which is consistent with the results reported in other studies (e.g., temperature change in mitochondria [ 19,20 ] ). The dispute about the data of temperature change in nano‐microregion indicates that the understanding of the phenomenon is different.…”
Section: Resultssupporting
confidence: 92%
“…measured a 3 °C increase in mitochondrial temperature in MCF‐7 cells upon PMA stimulation. [ 19 ] By contrast, D. Chretien et al. used MitoThermo Yellow, a temperature organic dye, as nanothermometers targeting the mitochondria and demonstrated that mitochondrial temperature in human embryonic kidney 293 cells increased by more than 10 °C at a constant external temperature of 38 °C when the respiratory chain was fully functional.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, other thermally sensitive energy transfer processes have been investigated to achieve better thermal resolutions with RE ions. [139,140] In addition, alternative materials have been engineered to present multiple emission bands, on their own or in synergy, for ratiometric thermometry, such as fluorescent proteins, [141] organic dyes, [142,143] nanopolymers, [144] quantum dots, [145,146] or gold nanoparticles. [147] A recent example of ratiometric thermometry makes use of the spectral shift produced in the emission of GFP.…”
Section: Techniques Based On Polarized Emissionmentioning
confidence: 99%
“…Finally, there remains substantial room for the development of advanced optical heaters and thermometers. Intracellular thermometry reported 1 °C or greater local temperature gradients in both stimulated and non-stimulated cells at the organelle level, such as in nuclei (Okabe et al 2012;Nakano et al 2017) (see also Vu et al 2021 for the controversial result), mitochondria (Okabe et al 2012;Kiyonaka et al 2013;Homma et al 2015;Nakano et al 2017;Huang et al 2018Huang et al , 2021Chrétien et al 2018Chrétien et al , 2020Savchuk et al 2019;Di et al 2021), and ER/SR (Kiyonaka et al 2013;Arai et al 2014;Itoh et al 2016;Hou et al 2017;Kriszt et al 2017;Oyama et al 2020). However, these experimental results largely contradict to the estimates based on the theories of macroscopic heat transfer, which expect the local temperature rises of the orders of 10 −4 to 10 −5 °C.…”
Section: Perspectivesmentioning
confidence: 99%